Impact of hydroclimatic variability on regional-scale landscape connectivity across a dynamic dryland region. (November 2018) - Bishop-Taylor, Robbi; Tulbure, Mirela G.; Broich, Mark
Graphical abstract: Highlights: Increasing hydroclimatic variability may affect regional-scale landscape connectivity. We modelled habitat networks across a dynamic, globally significant dryland region. Connectivity increased by two orders of magnitude between severe drought and flood. Habitat networks displayed resistance to drought despite decreases in surface water. Connectivity indicators may assist in guiding conservation in dynamic landscapes. Abstract: In dynamic dryland regions, accounting for spatiotemporal landscape dynamics is essential to understanding how ecological habitat networks are affected by hydroclimatic variability at regional or sub-continental scales. Here we assess how changes in the distribution and availability of surface water influence potential landscape connectivity for water-dependent organisms by combining graph theory network analysis with a Landsat-derived, seasonally continuous 25-year surface-water time-series. We focused on Australia's Murray Darling Basin (MDB), a globally significant and ecologically stressed 1 million km 2 semi-arid region recently affected by two unprecedented hydroclimatic extremes: the 1997–2010 Millennium Drought and 2010–2012 La Niña floods. We constructed potential habitat networks for two dispersal abilities using circuit theory resistance distances, and used 'habitat availability' graph theory metrics as indicators of regional-scale connectivity. We analysed 792 unique potential habitat networks containing over 6.6 million nodes, making our study one of the largest spatially explicit ecological network analyses yet conducted. Our indicators of connectivity revealed consistently positive but spatially heterogeneous relationships between flooded habitat area and landscape connectivity. Connectivity increased by over two orders of magnitude along the spectrum from severe drought to flood, associated with a transition from connectivity driven by intra-habitat or short-distance dispersal during drought to long-distance dispersal during wet conditions. Reductions in connectivity during drought were lower than expected given equivalent decreases in surface water habitat area, suggesting habitat network structure provides a degree of resistance to dry conditions. By providing insights into the processes driving connectivity during different phases along the drought-flood spectrum, our approach may assist in guiding conservation management aimed at maintaining or improving landscape connectivity within dynamic environments faced with increasing hydroclimatic variability.